The in vitro investigation of SARS-CoV-2, main protease (Mpro) exposure on glucose handling in skeletal muscle and liver cells - Nhau, Praise Tatenda (Rhodes University, 2026)
Despite evidence demonstrating risks of developing type 2 diabetes mellitus (T2DM) because of SARS-CoV-2, there is however insufficient scientific data available to elucidate the relationship between T2DM and COVID-19. The occurrence of multiple organ failure in COVID-19 patients highlights the importance of comprehending the cellular and molecular mechanisms of host cell factors exploited by SARS-CoV-2 to increase the risk of developing diabetes mellitus. Current literature associates obesity, inflammation and stress with insulin resistance, conditions that COVID-19 is known to induce suggesting a possible link to T2DM. Additionally, SARS-CoV-2 infection is associated with persistent organ damage due to systemic inflammation, which may contribute to long-term metabolic disruptions. Therefore, this in vitro study explored the perceived relationship between SARS-CoV-2 and diabetes mellitus by utilizing the SARS-CoV-2 Main protease (Mpro) to investigate its effects on key insulin-sensitive cells, C2C12(skeletal muscle) and HepG2(liver) cell lines. The aim was to uncover specific molecular mechanisms that may contribute to the development of the new-onset diabetes mellitus observed in patients post- COVID-19.
Keywords: Uncatalogued